An examination of selected works for high school euphonium students: Conqueror by Leonard B. Smith, In the Hall of the Mountain King by Edvard Grieg, Allerseelen by Richard Strauss, Pearl by H.A. Vandercook, Andante et Allegro by J. Ed. Barat, Andante et Allegro by J. Guy Ropartz, and Morceau Symphonique by Alexandre Guilmant - Keller, Travis Lee (Kansas State University, 2009)
This report is intended for teachers to use when preparing euphonium solo literature with their students. The solos selected for this report encompass a wide variety of styles and technical abilities, with each solo studied in four sections: Historical Background, Theoretical and Technical Considerations, Suggested Practice, and Educational Gains and Values. The solos studied in this report include Conqueror by Leonard B. Smith, In the Hall of the Mountain King by Edvard Grieg, Allerseelen by Richard Strauss, Pearl by H.A. Vandercook, Andante et Allegro by J. Ed. Barat, Andante et Allegro by J. Guy Ropartz, and Morceau Symphonique by Alexandre Guilmant.
Keywords: Euphonium; Repertoire; Survey; Baritone; Music (0413)